Juegos de mesa como recurso didáctico para el desarrollo de la comprensión oral en educación inicial - Punina Ramos, Reveca Inés (2025)
This review article explores the role of board games as didactic tools to enhance oral comprehension in 3- to 5-year-old children. Given that oral comprehension is fundamental in cognitive and socioemotional development during early childhood, this study analyzes how board games contribute to this process through pedagogical theories such as those of Vygotsky and Piaget. Descriptive methodology was used, with the PRISMA 2020 protocol, selecting 31 articles from various databases that met the inclusión and exclusion criteria that allowed us to elucidate the relevant studies to identify the impact of these games on linguistic and social interaction skills. The results suggest that board games not only promote oral and cognitive development, but also social interaction, critical thinking, problem solving, self-management in children, linguistic comprensión, phonological articulación. In addition, limitations are observed, such as the lack of parental involvement in the use of educational resources of these games. This article highlights the importance of conducting more studies to adapt board games to educational contexts and maximize their effectiveness as a learning strategy in early education.